Relaxin-encapsulated polymeric metformin nanoparticles remodel tumor immune microenvironment by reducing CAFs for efficient triple-negative breast cancer immunotherapy - Hongyan Zhang; Liying Chen; Yue Zhao; Ningchao Luo; Jingbin Shi; Shujun Xu; Lisha Ma; Menglin Wang; Mancang Gu; Chaofeng Mu; Yang Xiong (Elsevier, 2023)
Cancer-associated fibroblasts (CAFs) are one of the most abundant stromal cells in the tumor microenvironment which mediate desmoplastic response and are the primary driver for an immunosuppressive microenvironment, leading to the failure of triple-negative breast cancer (TNBC) immunotherapy. Therefore, depleting CAFs may enhance the effect of immunotherapy (such as PD-L1 antibody). Relaxin (RLN) has been demonstrated to significantly improve transforming growth factor-β (TGF-β) induced CAFs activation and tumor immunosuppressive microenvironment. However, the short half-life and systemic vasodilation of RLN limit its in vivo efficacy. Here, plasmid encoding relaxin (pRLN) to locally express RLN was delivered with a new positively charged polymer named polymeric metformin (PolyMet), which could increase gene transfer efficiency significantly and have low toxicity that have been certified by our lab before. In order to improve the stability of pRLN in vivo, this complex was further formed lipid poly-γ-glutamic acid (PGA)/PolyMet-pRLN nanoparticle (LPPR). The particle size of LPPR was 205.5 ± 2.9 nm, and the zeta potential was +55.4 ± 1.6 mV. LPPR displayed excellent tumor penetrating efficacy and weaken proliferation of CAFs in 4T1luc/CAFs tumor spheres in vitro. In vivo, it could reverse aberrantly activated CAFs by decreasing the expression of profibrogenic cytokine and remove the physical barrier to reshape the tumor stromal microenvironment, which enabled a 2.2-fold increase in cytotoxic T cell infiltration within the tumor and a decrease in immunosuppressive cells infiltration. Thus, LPPR was observed retarded tumor growth by itself in the 4T1 tumor bearing-mouse, and the reshaped immune microenvironment further led to facilitate antitumor effect when it combined with PD-L1 antibody (aPD-L1). Altogether, this study presented a novel therapeutic approach against tumor stroma using LPPR to achieve a combination regimen with immune checkpoint blockade therapy against the desmoplastic TNBC model.